The role of financial analysis in financial risk management and forecasting financial failure - Study of the case of The Great Belgeth Mills Souk Ahras - - kalleche, meriam; bahloul, nourelddine (Journal of Research in Finance and Accounting, 2021)
The study aimed to use financial analysis to manage financial risk and predict financial failure by focusing on some financial indicators, and forecasting models (sherrod, kida, altman) that give a financial analyst a vision of determining the financial position of The Great Belgeth Mills Based on Financial Statements 2016-2018. The study found that the results of the organization's performance through the negative indicators that appeared on it confirm its prediction of failure, so it had to take the necessary measures to manage the financial risks it faces by addressing weaknesses and taking advantage of the strengths.